Matematică
adamadina56
17

a) ([latex] \frac{2}\sqrt{3} [/latex] + [latex] \frac{3}\sqrt{2} [/latex] ) x 6 - ( [latex] \frac{1}\sqrt{12}[/latex] - [latex] \frac{1}\sqrt{8} [/latex] ) * [latex] \sqrt{24} [/latex] =

+1
(2) Răspunsuri
asdfghjkl123

[latex]\frac{2\sqrt2+3\sqrt3}{\sqrt6}*6-\frac{\sqrt2-\sqrt3}{\sqrt{24}}*\sqrt{24}=[/latex] [latex]=2\sqrt{12}+3\sqrt{18}-\sqrt2+\sqrt3=[/latex] [latex]=4\sqrt3+9\sqrt2-\sqrt2+\sqrt3=5\sqrt3+8\sqrt2[/latex]

balantudor

[latex]= (\frac{2 \sqrt{3} }{3} + \frac{3 \sqrt{2} }{2})*6 - \frac{ \sqrt{2}- \sqrt{3} }{ \sqrt{24}} * \sqrt{24} \\\\ = \frac{ 4\sqrt{3}+6 \sqrt{2} }{6} * 6 - \sqrt{2} + \sqrt{3} \\\\ = 4\sqrt{3}+6 \sqrt{2} - \sqrt{2} + \sqrt{3}\\\\ = 5 \sqrt{2} + 5 \sqrt{3} [/latex]

Adaugă răspuns